INTEGRATED SMALL AND MEDIUM INDUSTRY DEVELOPMENT STRATEGY OF MILKFISH BRAIN IN GRESIK DISTRICT - Andini Nurwulandari; Hasanudin Hasanudin; Edi Sugiono; Suryono Efendi; Sugito Efendi (Jurnal Info Sains : Informatika dan Sains, 2022)
Small and Medium Enterprises (SMEs) are important as one of the economic drivers of Gresik Regency because they help absorb labor and work towards poverty alleviation. On the other hand, UKM milkfish brain in Gresik has many obstacles including marketing, product production does not last long and the production process is still manual. The purpose of this community service is to identify the characteristics of UKM milkfish brain in Gresik district, to understand the real situation faced by UKM entrepreneurs. After obtaining an overview or actual situation, the internal and external environmental conditions of milkfish brain UKM were analyzed, and several alternative development strategies were selected as internal factors for the development of UKM milkfish brain, the Regent. Marketing of UMKM milkfish brain Gresik is growing and stable and requires a marketing strategy that needs to be strengthened internally with a competitive advantage for business development. Another priority strategy is to maintain product prices and improve quality to gain consumer loyalty. This requires segmentation and market segmentation as well as more publicity through online media